BUDAYA MEMBACA DI KALANGAN ANAK MUDA - Hasanah, Umi Ma'rufah Uswatun (Candi)
Umi Ma?rufah Uswatun Hasanah. Reading Culture Among Youth. Objectives (1) To know the culture of reading among young people. (2) To find the cause of the low. Reading culture among teens remains low. And this is necessary and shall be enhanced. Starting from the awareness of the adolescent to change his habits to want familiar with books that can provide insight. By reading, will make us as human beings who have insight and be far from folly. If we are away from ignorance, would be far from poverty. So the welfare of the nation Indonesia will be better.